MTHFR C677T polymorphism increases MTX sensitivity via the inhibition of S-adenosylmethionine and de novo purine synthesis. (25th January 2019) - Wang, Yi-Cheng; Wu, Ming-Tsung; Tang, Feng-Yao; Chen, Der-Yuan; Ko, Hsin-An; Shane, Barry; Huang, Wen-Nan; Chiang, En-Pei Isabel
Abstract : Objective: Currently, no guidelines are established for pharmacogenomic testing involving folate metabolic genes in long-term disease-modifying antirheumatic drugs' (DMARD) therapies. We carefully investigated how common genetic variations in methylenetetrahydrofolate reductase ( MTHFR ) influence cellular metabolic kinetics in response to methotrexate (MTX).Designs: Two distinct cell models: HepG2 with stabilized MTHFR inhibition using shRNA delivered by a Lentiviral vector; and Epstein–Barr virus transformed human lymphoblasts expressing MTHFR polymorphic allele 677C and 677T were used. Disease activity and DMARD use were compared between MTHFR- 677CC, CT and TT rheumatoid arthritis (RA) patients in a cross-sectional study ( n =120).Results: Compared with MTHFR -CC, MTHFR -TT carriers had lower mean weakly MTX dose (9.8 ± 3.3 compared with12.1 ± 3.5, P <0.05). More MTHFR- TT carriers (8/11, 73%) reported MTX-related side effects compared with MTHFR- 677CC (32/57, 56%) and MTHFR -677CT (30/51, 59%). No genotypic difference was found in other DMARDs. At the same dose of MTX, lymphoblasts were more sensitive in cell survival, protein and thymidine syntheses whereas HepG2 models were more susceptible to the inhibition of S -adenosylmethionine (adoMet) synthesis. MTHFR -C677T altered protein turnover and folate mediated 1-carbon metabolic fluxes in lymphoblasts with and without MTX. MTHFR function significantly affected transmethylation fluxes and adoMet homeostasis but not nucleotide biosyntheses in MTX-treated HepG2 cell-lines.Conclusion: Combining cell models, kinetic studies, and genetic tests in humans, the present study gives insight on how MTHFR effects hepatic transmethylation homeostasis during MTX therapy. We provide platforms that help predict the genetic impact on antifolate drugs, and further delineate tissue-specific target pathway in DMARD therapies. We suggest that genetic factors should be taken into account in clinical practice.